Mathematical modeling and statistical analysis of breast cancer drugs using M-polynomial indices for the physical properties - Qasem M. Tawhari; Muhammad Naeem; Saba Maqbool; Abdul Rauf; Oladele Oyelakin (Scientific Reports)
Abstract This study computes M-polynomial indices for Daunorubicin, an anthracycline antibiotic, is a potent anticancer agent used in treating various malignancies, including acute myeloid leukemia, acute lymphoblastic leukemia and breast cancer. We calculated M-polynomial indices using the edge partition of graphs based on degree and adjacency matrix. A Python code is developed based on an adjacency matrix to efficiently compute the indices that reduce calculation time from days to minutes and eliminate human error. Quantitative structure-property relationships are established using Multiple Linear, Ridge, Lasso, ElasticNet and Support Vector Regression in Python software to predict breast cancer drugs’ physical properties. Our results demonstrate that M-polynomial indices accurately predict physical properties, providing valuable insights into structural requirements for optimal anticancer activity. Additionally, we proposed the models against each physical property. This research facilitates the design of novel cancer therapeutics and enables the prediction of physical properties for uncharacterized drugs.